Formation of Virtual Mothers' Group Communication in the Management of Chickenpox: An Analysis Based on George Homans' Group Formation Theory - Rafika Hani Hani; Leila Mona Ganiem (Jurnal Bisnis dan Komunikasi Digital, 2026)
Chickenpox epidemic encourages the formation of the virtual group in school area as mediator in handling and changing the information. This research analyzes the construction process of virtual community "Ananda Sakit Cacar 1A" used WhatsApp by the mothers in SDIT  Asy Syafii Jakarta. This research adopts qualitative approach with study case method. The data collection technique by observation and depth interview to nine members of the group. The result found that the group formation by George Homans theory start from activity by reporting and discussing the Chickenpox symptoms in parents of student primary group, intent interaction that initiative to make a special group, and the anxious sentiment, solidarity and needs of mental support among the mothers. The research conclusion is the virtual community function use to facilitate the health information exchange. It is also important to support emotional system for mothers in handling of children health crisis.  This kind of virtual community can be the effective collaboration model between parents and school in managing the infectious disease outbreak.